Características del diagnóstico y tratamiento de la tuberculosis pulmonar en pacientes con y sin diabetes mellitus tipo 2 - Carrión Torres, Omar Jesús (2016)
To determine whether there are demographic, clinical and radiological differences among patients with pulmonary tuberculosis (TB) and patients with TB and type 2 diabetes mellitus (DM2 + TB).